Cytokine Adsorption onto the Modified Carbon Sorbent Surface in vitro in Peritonitis - T. I. Dolgikh; L. G. Pyanova; O. N. Baklanova; V. T. Dolgikh; L. S. Luzyanova; S. I. Filippov; T. F. Sokolova; A. N. Salanov; A. V. Glushchenko; A. V. Yershov; B. A. Reis; V. A. Likholobov (Общая реаниматология)
Objective: to evaluate the efficiency of cytokine sorption with carbon with a locally aminocaproic acid-modified surface from the plasma of patients with general purulent peritonitis. Materials and methods. The material of the investigation was the plasma obtained during plasmapheresis in 10 patients with acute pancreatitis complicated by pancreonecrosis and general purulent peritonitis, which was used to estimate before and after sorption the content of the cytokines: interleukin (IL)-1/8, IL-4, and IL-8 by enzyme immunoassay. The sorption properties of carbon hemosor-bent and aminocaproic acid-modified sorbent were comparatively evaluated. Results. Aminocaproic acid-induced modification of the carbon adsorbent surface with its further polycondensation results in the higher content of superficial functional groups (oxygen- and nitrogen-containing) that enhance the hydrophility of the surface and the specific pattern of sorption, thus acting as a means for controlling and regulating the plasma concentration of regulatory proteins, primarily the proinflammatory cytokine IL-1^3, the chemokine IL-8 and the T-helper cell clone cytokine IL-4.